Optimization of Casemix System to Increase Revenue of Bunda Medika Jakabaring Hospital - Saraswati, Nadya Ayu; Purwadhi, Purwadhi; Lestari, Yuniati (CV. Civiliza Publishing, 2025)
This study aims to determine the procedures for implementing the casemix system at Bunda Medika Jakabaring Hospital and its impact on hospital revenue, as well as to identify challenges and strategies for optimizing the casemix system to increase revenue. The method used is descriptive research with a qualitative approach, involving participants from various hospital units directly related to the operation and implementation of the casemix system. The research findings indicate that the implementation of the casemix system involves structured administrative and technical processes, from patient data validation to claim submission to BPJS, supported by information technology to ensure smooth operations. The casemix system changes the payment pattern for services to be based on case complexity, directly impacting hospital revenue by requiring meticulous documentation and coding. Key challenges include incomplete data, coding errors, lack of coordination between units, as well as limitations in human resources and technical constraints in the information system. Optimization strategies focus on strengthening documentation, regular training for medical staff, internal audits, comprehensive data validation, and enhancing cross-unit collaboration, along with information technology support to accelerate the claims process and sustainably increase revenue.